2017
DOI: 10.1007/s11104-017-3528-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus-mobilizing bacteria on tomato growth and soil microbial activity

Abstract: Aims The aim of our study was to clarify whether inoculating a soil with Pseudomonas sp. RU47 (RU47) bacteria would stimulate the enzymatic cleavage of organic P compounds in the rhizosphere and bulk soil, promoting plant growth. Adding either viable or heat treated RU47 cells made it possible to separate direct from indirect effects of the inoculum on P cycling in soil and plants. Methods We performed a rhizobox experiment in the greenhouse with tomato plants (Solanum lycopersicum) under low P soil conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 85 publications
0
28
0
1
Order By: Relevance
“…Phosphorus concentrations were analysed colourimetrically (Murphy and Riley, 1962) using a spectrophotometer (712 nm). The ratio of recovered P to added P was used to calculate the P mic concentration as follows (Nassal et al, 2018):…”
Section: 1mentioning
confidence: 99%
“…Phosphorus concentrations were analysed colourimetrically (Murphy and Riley, 1962) using a spectrophotometer (712 nm). The ratio of recovered P to added P was used to calculate the P mic concentration as follows (Nassal et al, 2018):…”
Section: 1mentioning
confidence: 99%
“…There is a growing interest in using P solubilizing bacteria as biofertilizers to increase the bioavailability of P in soils used for crop production and to enhance the efficiency of P fertilizer applications ( Figure 1D). Increases in plant performance and/or yield after an inoculation with P-solubilizing bacteria have been shown for many agronomically important crop species, including corn [153], soybean [154], wheat [154,155], rapeseed [156], mung bean [157], and tomatoes [158]. While the periodic application of P fertilizer has adverse effects on the structure and function of phosphate-solubilizing bacterial communities, the opposite is true when little or no superphosphate is applied [159].…”
Section: Phosphate Solubilizing Bacteria and Their Potential To Incrementioning
confidence: 99%
“…Researches with growth regulators and hormones associated with nutrient aim to accelerate the development of plants. The application of such elements in the early stages of plant development can stimulate root growth which would provide faster recovery after a period of water stress; greater resistance to pests, diseases and nematodes; and more rapid and uniform establishment of plants (Nassal et al 2018; du Jardin 2015; Zhao 2012; Bashan and de-Bashan 2010; Spaepen and Vanderleyden 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that innoculation of Pseudomonas sp. RU49 in soil associated with the increased posphatase activity in the soil and improved tomato plant growth (Nassal et al 2018). The objectives of this study were to (1) evaluate the effectiveness of 19 microbial isolates which have P solubilizer and plant growth regulator characters in enhancing plant growth and yield of tomato (Palupi variety) grown in pots, and (2) molecularly identify the most effective isolates in improving tomato growth based on 16s rDNA sequences.…”
Section: Introductionmentioning
confidence: 99%